BK Channel-Mediated Microglial Phagocytosis Alleviates Neurological Deficit After Ischemic Stroke - Huang, Shuxian; Chen, Tingting; Suo, Qian; Shi, Rubing; Khan, Haroon; Ma, Yuanyuan; Tang, Yaohui; Yang, Guo-Yuan; Zhang, Zhijun (Frontiers in Cellular Neuroscience, 2021)
Microglial phagocytosis benefits neurological recovery after stroke. Large-conductance Ca2＋-activated K+ currents are expressed in activated microglia and BK channels knockout aggravates cerebral ischemic injury. However, the effect of BK channels on microglial phagocytosis after ischemic stroke remains unknown. Here, we explored whether BK channels activation are beneficial for neurological outcomes through microglial phagocytosis after ischemic stroke. ICR mice after transient middle cerebral artery occlusion (tMCAO) were treated with DMSO, BK channels activator NS19504 and inhibitor Paxilline. The results showed decrease of BK channels expression after tMCAO. BK channels activator NS19504 alleviate neurological deficit after experimental model of tMCAO in mice compared to the control. Furthermore, we treated primary microglia with DMSO, NS19504 and Paxilline after oxygen glucose deprivation (OGD). NS19504 promoted primary microglia phagocytosing fluorescent beads and neuronal debris, which reduced neuronal apoptosis after stroke. These effects could be reversed by BK channels inhibitor Paxilline. Finally, NS19504 increased relative phosphorylated extracellular signal-regulated kinases 1/2 expression compared to Paxilline group at third day after stroke. Our findings indicate that microglial BK channels are a potential target for acute stage of ischemic stroke therapy.